Combined transcriptome and metabolome analysis of Polygonatum cyrtonema Hua in response to Botrytis deweyae infection - Fuqiang Yin; Wanli Ma; Wanli Ma; Zhien Xiao; Yuxin Liu; Tiantian Guo; Yue Yuan; Shaotian Zhang; Guoli Li; Ming Liu (Frontiers in Plant Science)
The fungal pathogen Botrytis deweyae, first identified as the causative agent of gray mold disease in China, has become a critical biotic constraint limiting the sustainable production of Polygonatum cyrtonema Hua in major cultivation regions. To investigate the physiological reactions and transcriptome gene changes of P. cyrtonema after B. deweyae infection, in this study, we investigated the defense enzyme activity, transcriptome differential genes (DEGs), and differential metabolites (DAMs) of P. cyrtonema. When B. deweyae invaded the leaves of P. cyrtonema, the activities of phenylalanine deaminase (PAL), catalase (CAT), and peroxidase (POD) increased. The most responsive Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways in the transcriptome were plant-pathogen interaction, plant hormone signal transduction, the mitogen-activated protein kinase (MAPK) signaling pathway, and phenylpropanoid biosynthesis (phenylpropanoid biosynthesis) metabolic pathways. Among the DEGs, AP2 ERF-ERFs, WRKYs, and C2H2 were highly predictive of transcription factors (TFs), with WRKYs being important TFs in the P. cyrtonema MAPK pathway. In the metabolome, coumaric acid, α-linolenic acid, and jasmonic acid (JA) are important metabolites that respond to B. deweyae infection. Correlation analysis between the transcriptome and metabolome revealed that phenylpropanoid metabolism and α-linolenic acid metabolism pathways are associated with the most significant response of P. cyrtonema to B. deweyae infection, with phenylpyruvate being an important metabolite in the phenylpropanoid metabolic pathway. Additionally, the observed upregulation of α-linolenic acid and JA synthesis suggests potential activation of JA-dependent induced systemic resistance (ISR) against B. deweyae, possibly mediated through downstream MYC transcription factors. These findings indicate that JA signaling contributes significantly to P. cyrtonema defense response against fungal infection. Our findings provide foundational insights that may support the development of disease-resistant cultivars or biostimulant strategies for P. cyrtonema and related medicinal plants.